Weakly injective dimension and Almost perfect rings (JOURNAL OF ADVANCES IN MATHEMATICS, 2013)
In this paper, we study the weak-injective dimension and we characterize the global weak-injective dimension of rings. After we study the transfer of the global weak-injective dimension in some known ring construction. Finely we study the transfer of almost perfect property in pullback and D+M constructions.